Analisis Bay’ Gharar Dalam Aplikasi Tiktok - Khatimah, Husnul; Nuradi, Nuradi; Amalia, Sinta; Kamilah, Faizah; Taslim, Humairah Az-Zahra (Iqtisad: Journal of Islamic Economic and Civilization, 2025)
The development of technology has had a huge impact on economic growth, especially with the emergence of online buying and selling platforms. Among those that are currently viral in Indonesia is TikTok with the TikTok Shop feature. This research is an analytical study with the aim of knowing the element of gharar in the TikTok Serok and TikTok Capit trade on the TikTok platform. Gharar is uncertainty in buying and selling transactions that can occur in the contract, object, price, and time of handover which is forbidden in Islam. Data from the research is obtained from the results of literature studies by reviewing journals, books, articles and documents which are then analyzed descriptively qualitative. The results of the study indicate that the unclear nature of the object purchased through live TikTok Serok and TikTok Capit is a gharar of the majhūl type of sale and al ma'jūz 'an taslīmih. Because this system can cause losses to buyers and sellers due to the uncertainty of each item and the price per item contained in a single claw or spade.